2006
DOI: 10.1017/s1047951106000151
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous connection of the right superior caval vein to the morphologically left atrium

Abstract: Anomalous drainage of the right superior caval vein into the morphologically left atrium as an isolated cardiac malformation is a rare anomaly. Most patients present with cyanosis. Thus far, about 20 cases have been reported in the literature. We report a case of cyanosis due to this malformation in a male neonate, which was complicated by the meconium aspiration syndrome. The malformation was diagnosed by echocardiography and cardiac catheterization. Surgery resulted in complete recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Drainage of the right SVC to the LA is an exceedingly rare congenital malformation of systemic veins [1]. In a previously published case report, Van Praagh and colleagues were able to identify 18 cases of LA drainage of the right SVC, and an additional seven cases of biatrial drainage of right SVC in viscera-atrial situs solitus [2].…”
Section: Discussionmentioning
confidence: 99%
“…Drainage of the right SVC to the LA is an exceedingly rare congenital malformation of systemic veins [1]. In a previously published case report, Van Praagh and colleagues were able to identify 18 cases of LA drainage of the right SVC, and an additional seven cases of biatrial drainage of right SVC in viscera-atrial situs solitus [2].…”
Section: Discussionmentioning
confidence: 99%
“…There are several cases of this defect in association with other congenital heart defects and heterotaxy, but through our review only 42 cases of this as an isolated anomaly have been reported in the English literature to date 1,3‐43 . Table 1 summarizes the reported cases as case number, year of publication, first author, age and gender of patient, presentation, method of diagnosis, and the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know just twenty cases were described [5], while the persistent left superior vena cava draining into the coronary sinus is relatively common. The concomitance of these two anomalies of systemic venous return is almost anecdotal, but while the persistent left superior vena cava is quite common and its morphogenesis is well known, for the right superior vena cava draining into the left atrium there are different theories about the embryogenesis.…”
Section: Discussionmentioning
confidence: 99%